Desarrollo de un aceite esencial de orégano (origanum vulgarel.) micro encapsulado , mediante secado por aspersión. - Andrade Imbago, Karen Pamela (2020)
In the present investigation, an essential oil of oregano (Origanum vulgare L.) microencapsulated was developed, for this the method of drying by aspersion was used, resorting to the equipment Spray Dryer model SD-303 of the Pilot Plant of the Department of Sciences of Food and Biotechnology (DECAB) of the National Polytechnical School; as encapsulating material a polymeric mixture of Arabic gum/maltodextrin with a percentage of 9.3 % and 18.7 % respectively was used. The study elements were selected according to a previously obtained research background. Through optimization, eight runs were established, and the control factors were feed flow of 0.6 L/h, 0.8 L/h, and 1 L/h and air inlet temperature at 160 ºC, 180 ºC, and 200 ºC. In the microencapsulated powders, antioxidants and oil retention and physical-chemical properties such as moisture, hygroscopicity, solubility, and flowability were analyzed. Subsequently, the Design Expert 8.0.6 program (Stad-Ease Inc., Minneapolis, USA) was used to process the data obtained, following the response surface design. Through optimization, the best run of the microencapsulated powder was determined with a feed flow of 0.6 L/h and temperature 200 °C presenting the following characteristics: 1351.70 μM Fe2+/g of sample antioxidant capacity, 92.10% essential oil retention and 88.53% yield.